2006
DOI: 10.1093/intimm/dxl088
|View full text |Cite
|
Sign up to set email alerts
|

TCR transgenic CD8+ T cells activated in the presence of TGF  express FoxP3 and mediate linked suppression of primary immune responses and cardiac allograft rejection

Abstract: Although CD4+CD25+FoxP3+ regulatory T cells play a role in allograft tolerance, the role of CD8+ cells with immunosuppressive function is less clear. To address this issue, spleen cells from Rag-1-deficient TCR transgenic (Tg) mice expressing a receptor for ovalbumin (OVA) in the context of MHC class I (OT1) were activated with OVA expressing antigen-presenting cell (APC) in the presence or absence of exogenous transforming growth factor beta (TGFbeta). TGFbeta inhibited the expression of IFN-gamma, granzyme B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
48
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 76 publications
14
48
1
Order By: Relevance
“…Recent studies have found that CD8 þ precursors can be induced to express FoxP3, with acquisition of induced regulatory T cell activity similar to CD4 þ CD25 þ FoxP3 þ cells. 58,59 In this study, we show that the administration of RSG enhances the expression of FoxP3 in the peritoneal cellular influx. The relative proportion of these FoxP3 þ cells that derive from natural or induced regulatory T cells will require further analysis.…”
Section: Discussionsupporting
confidence: 52%
“…Recent studies have found that CD8 þ precursors can be induced to express FoxP3, with acquisition of induced regulatory T cell activity similar to CD4 þ CD25 þ FoxP3 þ cells. 58,59 In this study, we show that the administration of RSG enhances the expression of FoxP3 in the peritoneal cellular influx. The relative proportion of these FoxP3 þ cells that derive from natural or induced regulatory T cells will require further analysis.…”
Section: Discussionsupporting
confidence: 52%
“…These observations that Tregs exhibit functional specificity provide support for the feasibility of using Tregs as immune modulators in the clinic, which would be severely compromised if they were nonspecific in their suppressive function. The capacity of Tregs to suppress effector T cell responses to distinct Ags if both Ags are presented by the same APC, as shown in this study and other reports (47,53,60,61), promises to expand the utility of Tregs for treatment of diseases, such as type 1 diabetes and multiple sclerosis, in which pathogenic T cells with specificities for multiple Ags are involved, without the need to identify each epitope.…”
Section: Few If Any Cd4supporting
confidence: 67%
“…After 4 -5 days, the cultures were harvested and assayed for lytic activity using the H-2 b tumor cell line (EL4, an MHC class II-negative T cell lymphoma) (44), E.G7-OVA (EL4 cell line that expresses the chicken OVA gene (44), and the H-2 d cell line (P815) as targets for the CTL assays. CTL activity was measured using a modification of published flow cytometry methods using CFSE-labeled targets (45,46) to directly count the number of viable target cells, as previously described (47). The ratio of viable Ag ϩ /Ag Ϫ cells in each experimental tube divided by the same ratio in the control tubes gives a measure of Agspecific cytotoxicity by the formula: percentage of specific cytotoxicity ϭ 100…”
Section: Induction and Assay Of Ag-specific Cd4mentioning
confidence: 99%
“…+ CD28 -cells [129][130][131][132], CD3 + CD4 -CD8 -cells [133,134] and naturally occurring CD4 + CD25 + T cells [135]. Given that both human and murine knock-outs for CD4…”
Section: Regulatory T Cellsmentioning
confidence: 99%